Public Debt-Growth Nexus: Threshold Effects on Selected Southeast Asian Countries - Wan-Yan, Lee; Jerome, Kueh (Universal Publishers - Boca Raton, Florida, USA, 2021)
The goal of this study is to analyzethe impact of the public debt threshold on economic growth in selected Southeast Asian countries (Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam) using annual data from 1996 to 2016. Empirical results suggest that there is a negative long-term connotation between public debt and economic growth through the estimator method of Pooled-Mean Group (PMG). Furthermore, Threshold Regression method is adopted to examine the different effects of public debt levels on economic growth as either below or above the threshold level. The results revealed that the public debt threshold level for the six Southeast Asian countries is approximately 68.31%. Public debt has a positive effect on development when debt is below the level of 68.31%. However, public debt will be detrimental to growth if the debt level exceeds the threshold.